2007
DOI: 10.1086/521424
|View full text |Cite
|
Sign up to set email alerts
|

Stromgren Photometry of Galactic Globular Clusters. I. New Calibrations of the Metallicity Index

Abstract: We present a new calibration of the Stroemgren metallicity index m 1 using red giant (RG) stars in a sample of Galactic globular clusters (GGCs: M92, M13, NGC 1851, 47 Tuc) that cover a broad range in metallicity (−2.2 ≤ [Fe/H] ≤ −0.7), are marginally affected by reddening uncertainties (E(B-V ) ≤ 0.04) and for which accurate u, v, b, y Stroemgren photometry is available to well below 1 Based in part on observations collected with the 1.54m Danish telescope operated at ESO (La Silla) and with the Nordic Optica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(143 citation statements)
references
References 77 publications
4
139
0
Order By: Relevance
“…These GCs also behave differently for what concerns Ba abundances. To show this, we used the Johnson UBVI photometry by Momany (unpublished photometry, reduced as in Momany et al 2003) for 47 Tuc and the Strömgren photometry by Grundahl for NGC 6752 (Calamida et al 2007) to reproduce the clear splits shown by Milone et al (2012Milone et al ( , 2013. We took the Ba abundances from D 'Orazi et al (2010), cross-identified the stars, and plotted the ones in common in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These GCs also behave differently for what concerns Ba abundances. To show this, we used the Johnson UBVI photometry by Momany (unpublished photometry, reduced as in Momany et al 2003) for 47 Tuc and the Strömgren photometry by Grundahl for NGC 6752 (Calamida et al 2007) to reproduce the clear splits shown by Milone et al (2012Milone et al ( , 2013. We took the Ba abundances from D 'Orazi et al (2010), cross-identified the stars, and plotted the ones in common in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7). -We used literature photometry in u, b, v, and y Strömgren bands (Grundahl et al 1999;Calamida et al 2007) to define a new color index ((u − y) + (v − b)). We found that the u versus (u − y) + (v − b) diagram is a powerful tool to identify the double RGB and SGB of NGC 1851 and showed that the faint-SGB is clearly connected with the red-RGB, while blue-RGB stars are linked to the bright-SGB (Fig.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The resulting photometry was calibrated using stars in common with the V, I Bellazzini et al (2001) catalog, covering an 8 × 8 field centered on the cluster. We also used publicly available Strömgren u, v, b, y photometry 1 of NGC 1851 from Grundahl et al (1999) and Calamida et al (2007). We refer the reader to that paper for details about observations and data reduction of Ströemgren photometry.…”
Section: Source Catalogs and Sample Selectionmentioning
confidence: 99%
“…To supplement this evidence, we used the Strömgren photometry by Grundahl (available through the database used by Calamida et al 2007) to plot the stars of the P, I, and E components in NGC 1851. The definition of the primordial (P), intermediate (I), and extreme (E) population in a cluster, based on 8 Note that the analysis considered here for ω Cen (Johnson & Pilachowski 2010) is not strictly consistent with the other determinations shown in the plot, which come from our FLAMES survey.…”
Section: The Complex Nucleosynthesis In Ngc 1851mentioning
confidence: 99%